Metasystox Induced Haematological Modulation In The South Indian Snakeheaded Channa striata - Sasikala, G (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTSnakeheaded Channa striata reared in freshwater of metasystox (1.7 mg L-1) for 15 d and 30 d. Evaluation of some of the haematological parameters showed that on exposure, haematocrit content (Ht), haemoglobin content (Hb), total erythrocyte count (RBC), neutrophil, basophil, lymphocyte values markedly increased and depressed monocyte values. Observations of blood parameters allows the most rapid detection changes in fish, which may be used as a diagnostic test for aquatic pollution